IMPLEMENTASI MODEL PROTOTYPE DALAM PEMBUATAN SISTEM INFORMASI PELAYANAN UMUM DAN KEPEGAWAIAN BERBASIS WEBSITE PELAYANAN (STUDI KASUS : DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN SANGGAU KALIMANTAN BARAT) - Firmansyah, Yoki; Maulana, Reza; Purwaningtias, Deasy; Linawati, Safitri; Jimi, Romuanus (Jurnal Khatulistiwa Informatika, 2023)
In the current era of globalization, information technology is advancing rapidly. Information technology is a solution to many problems that occur in government and private agencies to improve performance and work processes in agencies. One of the agencies that can utilize Information Technology is the Sanggau District Education and Culture Office, especially in the service sector. Based on observations, interviews and collections carried out, there are problems experienced by the Sanggau Regency DISDIKBUD such as the lack of use of ICT, a lot of non-computerized recording in providing services, storage and making reports so that during the work process there are often delays in searching for data and the accuracy of the data is in doubt. So to solve this problem, a computerized information system is needed so that performance is better, and services are more effective in terms of time, and efficient in terms of costs compared to the previous system. The system development models implemented are prototype models and information systems. which is made on a website basis and it is hoped that the implementation of this model can solve the problems that are currently occurring.